Aspects of bridge‐ground seismic response and liquefaction‐induced deformations. (7th January 2020) - Qiu, Zhijian; Ebeido, Ahmed; Almutairi, Abdullah; Lu, Jinchi; Elgamal, Ahmed; Shing, P. Benson; Martin, Geoffrey
SUMMARY: Considerable bridge‐ground interaction effects are involved in evaluating the consequences of liquefaction‐induced deformations. Due to seismic excitation, liquefied soil layers may result in substantial accumulated permanent deformation of sloping ground near the abutments. Ultimately, global response is dictated by the bridge‐ground interaction as an integral system. However, a holistic assessment of such response generally requires a highly demanding full three‐dimensional (3D) model of the bridge and surrounding ground. As such, in order to capture a number of the salient involved mechanisms, this study focuses on the longitudinal seismic performance of a simpler idealized configuration, motivated by details of an existing bridge‐ground configuration. In this model, a realistic multilayer soil profile is considered with interbedded liquefiable/nonliquefiable strata. The effect of the resulting liquefaction‐induced ground deformation is explored. Attention is given to overall deformation of the bridge structure due to lateral spreading in the vicinity of the abutments. The derived insights indicate a need for such global analysis techniques, when addressing the potential hazard of liquefaction and its consequences.